Can United States intelligence community analysts telework?. Issue 6 (18th September 2020) - Gioe, David V.; Hatfield, Joseph M.; Stout, Mark
ABSTRACT: This article argues that United States Intelligence Community analysts can and should periodically telework as routine professional development and as a research supplement to traditional all-source intelligence analysis. We offer four key benefits to tapping into this reservoir of unclassified information that would improve the quality of the intelligence product, enable better liaison and academic exchange, and steward the profession. We conclude that an overdue rebalancing of classified and publicly available sources could be aided by telework, but only once analysts break free from 'the cult of the SCIF' will publicly available information receive the analytical attention that it deserves.